2013
DOI: 10.1159/000354835
|View full text |Cite
|
Sign up to set email alerts
|

Serum Growth Differentiation Factor 15 Levels in Newly Diagnosed Multiple Myeloma Patients

Abstract: Background/Aims: Multiple myeloma (MM) is a hematological cancer associated with increased clonal malignant plasma cells. Growth differentiation factor 15 (GDF 15) is a protein that is highly expressed in the bone marrow mesenchymal stem cells of patients with MM. This study investigated whether the clinical stage of the disease, treatment response and survival are affected by pretreatment serum GDF 15 levels. Methods: Serum GDF 15 levels were measured in 35 newly diagnosed MM patients and 27 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
7
16
0
Order By: Relevance
“…These data are comparable to those of our previous study [6]. Interestingly, Tarkun et al [1] examined the putative link between GDF15 level and response to treatment and found that the serum GDF15 level was significantly higher in patients with partial response or less than partial response to treatment compared to those with at least very good partial response. However, unlike our previous work, this study failed to demonstrate an impact of the GDF15 level on patient survival.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…These data are comparable to those of our previous study [6]. Interestingly, Tarkun et al [1] examined the putative link between GDF15 level and response to treatment and found that the serum GDF15 level was significantly higher in patients with partial response or less than partial response to treatment compared to those with at least very good partial response. However, unlike our previous work, this study failed to demonstrate an impact of the GDF15 level on patient survival.…”
supporting
confidence: 89%
“…In this issue of Acta Haematologica , Tarkun et al [1] report that the level of serum growth differentiation factor 15 (GDF15) is a prognostic factor in multiple myeloma and may predict response to treatment.…”
mentioning
confidence: 99%
See 3 more Smart Citations